Effect of some factors on characteristics of charolais beef production in ultrasound measuring - Polgár, József Péter; Török, Márton; Kovács, Ákos; Bene, Szabolcs (Animal welfare, Ethology and Housing Systems (AWETH), 2020)
A constant challenge of the beef breeding is to produce an end-product that meets the market’s needs. It is essential that breeders should continously test herds in order to make this production economic. The proper and responsible data recording, which belong to one of the fundamental conditions for the success of breeding work, requires objective measurement methods. Charolais is one of the most widely-known large beef cattles with excellent meat-producing ability and the ability to gain weight. The primary product is the cut body, the boned meat, so it is advisable to display the parameters of the meat production capacity in the process of estimating the breeding value. During previous practice the information needed for this came primarily from studying offspring production, which is a time-consuming and expensive process (Williams, 2002). However devices (UH, CT, MR)- which can record data quickly and simply with high security and precision- have become increasingly available with the advancement of technology. The use of ultrasound is a noninvasive and reliable method (Williams, 2002). Ultrasonic measurement can be performed on live animals under field conditions (Tőzsér et al., 2005). The ribeye cross-section, the fat thickness under the skin on the rib eye area and the tail are among the tested parameters. P8 data is used in BREEDPLAN breeding value estimation structures. The use of the operating application only emerges in connection with experimental activities in domestic practice. The testing is performed by the Association during the rearing process of the breeding animals and the evaluation of the data is in progress.